Identifying cross-border functional areas: conceptual background and empirical findings from Polish borderlands. Issue 12 (2nd December 2022) - Jakubowski, Andrzej; Trykacz, Karolina; Studzieniecki, Tomasz; Skibiński, Jakub
ABSTRACT: Preparations for the EU's post-2020 Multiannual Financial Framework have brought increased interest to the functional approach as a major paradigm of the EU policies towards cross-border areas. This approach aims to focus cross-border programmes on territories where there is a high degree of cross-border interaction. Cross-border functional areas (CBFAs) can be a potential instrument for this, fostering further reduction of cross-border barriers and enhancing flows of people, goods, materials and knowledge. However, certain aspects of this notion are rather vague. This includes both the way how to turn the rather discursive concept of the CBFA into more material-institutional practices, and how CBFAs can be identified in practice to successfully implement the EU's cohesion policy. This paper debates the concept of the CBFA and proposes understanding CBFAs as spatially specific territorial complexes, located on two (or more) sides of a state border(s) that are not defined by administrative borders, but by cross-border functional linkages, a system of cooperative relationships and the existence of governance mechanisms. The paper proposes a novel approach for CBFA's identification based on a four-level model, taking into account the selected criteria. The proposed framework enabled to identify CBFAs and potential CBFAs at the borders of Poland.